The C-BIM Model in Improving Reading, Writing, and Critical Thinking Skills: Outcome and Perception - Haerazi Haerazi; Sadaf Dehghani; Umi Rachmawati; Dedi Irwansyah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
This study investigates the culture-based instructional materials (C-BIM) model to improve students’ reading and writing skills viewed from critical thinking skills at the junior-high-school in Indonesia. This study is a mixed-method employing the explanatory sequential design. The data are in the form of quantitative and qualitative data. The quantitative data are collected first and followed by the quantitative one. The research instruments are in the form of reading and writing tests, questionnaires, and interview sheets. The test is used to see the students’ reading and writing achievements. Meanwhile, the questionnaire is utilized to determine the students’ and teachers’ intercultural awareness and perception of incorporating cultures in teaching materials. The data of reading-writing achievement are analyzed using descriptive and inferential statistics. Thus, the data of students’ and teachers’ cultural awareness and perception are gained by applying qualitative steps: analysis, reduction, coding, interpretation, and conclusion. Based on the result of the research, this study indicates that the C-BIM model significantly affects students’ reading and writing skills. Also, it has an interaction between teaching materials and critical thinking skills. Researchers elaborate on those in the discussion part of this article regarding the students' intercultural competence and perception.